The impact of using the internet in promoting Romanian industry - PASTIU, Carmen Adina (Annals of Spiru Haret University. Economic Series, 2012)
Central element of the marketing mix, advertising can differentiate the companies in Romanian industry through the strategy used by each company. The present paper summarises the results of a qualitative research conducted in 15 companies acting in food, mechanical processing, textile, leather, and footwear industries. Throughout this study the benefits of using online promotion were highlighted and a diagnosis regarding the use of the Internet for promoting products in Romanian industry was performed.